(untitled) (El-Wahat Journal for Research and Studies, 2025)
Phoneme Theory Is One Of The Modern Theories Codified By The West Through Its Treatment By Specialists And Defining Principles For It. In Our Study, We Seek To Exploit The Principles Of This Theory And Approach It With What Is Stated In Muthalathat Qutrub In Reading, By Looking At Selected Living Examples Of Three Lexical Units In A Poetic Line That Differ In One Phoneme. This Study Revealed That Muthalathat Qutrub Truly Embody The Principles Of The Phoneme Theory; The Change Of One Vowel In A Lexical Unit Leads To A Change In Its Meaning. Keywords: Phoneme Theory, Alefone, Muthalathat, The Vowels, Lexical Unit.